INTEGRATION OF DIFFERENTIAL EQUATION FOR CELESTIAL BODIES’ MOTION BY THE RUNGE-KUTT METHOD IN THE THIRD ORDER - Bazyey, O. A.; Kara, I. V. (Одеські астрономічні публікації, 2017)
Equations of celestial bodies’ motion in coordinates are solved by numerical Runge-Kutt method. The coefficients of Runge-Kutt method in the 10th order are obtained. The solutions are compared by methods of different order, for this purpose Runge-Kutt methods of the 4th, 5th and 10th orders have been realized in programs.